Experimental Investigation of Mechanical Properties of PVC Polymer under Different Heating and Cooling Conditions - Sarkawt Rostam; Alan Kareem Ali; Firdaws Haidar AbdalMuhammad (Journal of Engineering)
Due to a widely increasing usage of polymers in various industrial applications, there should be a continuous need in doing research investigations for better understanding of their properties. These applications require the usage of the polymer in different working environments subjecting the material to various temperature ranges. In this paper, an experimental investigation of mechanical properties of polyvinyl chloride (PVC) polymer under heating and cooling conditions is presented. For this purpose standard samples are prepared and tested in laboratory using universal material testing apparatus. The samples are tested under different conditions including the room temperature environment, cooling in a refrigerator, and heating at different heating temperatures. It is observed that the strength of the tested samples decreases with the increasing of heating temperature and accordingly the material becomes softer. Meanwhile the cooling environments give a clear increasing to the strength of the material.